An Analysis of The Ease of Use of Non-Chat Whatsapp Applications Among The Elderly Using The System Usability Scale (SUS) Method - Syahrul Ramadhan; Irma Santikarama; Dea Destiani (International Journal Labs, 2026)
The increasing use of digital communication technology has created challenges for elderly users, particularly in accessing and operating non-chat WhatsApp applications that provide various digital services beyond conventional messaging functions. Limited digital literacy, unfamiliar interface designs, and age-related barriers may affect the usability and acceptance of these applications among older adults. This study aims to analyze the ease of use of non-chat WhatsApp applications among elderly users using the System Usability Scale (SUS) method. This research employed a quantitative approach by collecting usability evaluation data from elderly respondents who had experience using non-chat WhatsApp applications. Data were obtained through SUS questionnaires consisting of ten standardized usability statements measured using a Likert scale. The collected data were analyzed to determine the overall usability score and identify the level of user acceptance based on SUS interpretation criteria. The results showed that the usability evaluation provided an overview of elderly users’ perceptions regarding application efficiency, learnability, and interaction convenience. The SUS score indicated the level of usability acceptance of non-chat WhatsApp applications, demonstrating the extent to which the interface design supports elderly users in completing digital service interactions. This study concludes that usability evaluation using the SUS method can provide an effective approach for identifying accessibility issues and improving the design of digital communication applications for elderly users. Future improvements should focus on simplified interfaces, clearer navigation structures, and user-centered design approaches to enhance digital inclusion among older adults.